2010
DOI: 10.1103/physreva.82.012106
|View full text |Cite
|
Sign up to set email alerts
|

Quantum and classical thermal correlations in theXYspin-12chain

Abstract: We investigate pairwise quantum correlation as measured by the quantum discord as well as its classical counterpart in the thermodynamic limit of anisotropic XY spin-1/2 chains in a transverse magnetic field for both zero and finite temperatures. Analytical expressions for both classical and quantum correlations are obtained for spin pairs at any distance. In the case of zero temperature, it is shown that the quantum discord for spin pairs farther than second-neighbors is able to characterize a quantum phase t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
199
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 238 publications
(203 citation statements)
references
References 49 publications
4
199
0
Order By: Relevance
“…Recent results showing that almost all (separable) quantum states actually have such nonclassical correlations [3] and that they can improve some computational tasks in comparison to when classical states are used [4,5] reinforce the relevance of such an issue. As a result, the last few years have witnessed an increasing number of articles discussing the quantification of these correlations [1,2,[6][7][8], their behavior under decoherence [9][10][11][12], and their relevance for quantum phase transitions [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Recent results showing that almost all (separable) quantum states actually have such nonclassical correlations [3] and that they can improve some computational tasks in comparison to when classical states are used [4,5] reinforce the relevance of such an issue. As a result, the last few years have witnessed an increasing number of articles discussing the quantification of these correlations [1,2,[6][7][8], their behavior under decoherence [9][10][11][12], and their relevance for quantum phase transitions [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Quantum discord [16,17] is a widely accepted one among them. The quantum discord plays an important role in the research of quantum correlations due to its potential applications in a number of quantum processes, such as quantum critical phenomena [18][19][20][21], quantum evolution under decoherence [22,23] and, as we just mentioned, the DCQ1 protocol [24]. To quantify the multipartite quantum correlations, generalizations of bipartite quantum discord to multipartite states have been considered in various aspects [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Quantum discord is a correlation measure aimed at quantifying all quantum correlations including entanglement. A key feature of QD is that in general it is not symmetric under exchange of the two subsystems 41 : measurement processes applied to the two different subsystems can lead to different values of discord. However, in the examples we will study the density matrices are symmetric with respect to the exchange of subsystem and so is the discord evaluated for the systems represented by these states.…”
Section: Quantum Discord and Classical Correlationsmentioning
confidence: 99%
“…The notion of QD has also been investigated, both from the theoretical 21,22 and the experimental side 23 , in the context of open quantum systems where it was shown that QD is generally more robust than entanglement to dissipation and thermal noise; moreover, QD is tightly related to complete positivity of quantum maps 24 . In the realm of many-body systems, the behavior of QD has been analyzed in relation to QPTs and thermal effects [25][26][27][28][29][30][31] . So far, the research has mostly concentrated on one-dimensional spin 1/2 models [25][26][27][28][29][30] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation